2016
DOI: 10.1097/wnp.0000000000000283
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic and Electrophysiological Evaluation of the Ulnar Nerve in Patients Diagnosed With Carpal Tunnel Syndrome

Abstract: Based on our study results, the ulnar nerve is affected electrophysiologically and morphologically in patients with CTS, especially those with advanced-stage CTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Some studies have shown that patients with CTS may have UN damage [ 16 , 17 ]. A study by Kang et al found that when patients with CTS underwent carpal tunnel release, the pressure in Guyon’s canal was reduced and the sensory conduction of the UN improved [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that patients with CTS may have UN damage [ 16 , 17 ]. A study by Kang et al found that when patients with CTS underwent carpal tunnel release, the pressure in Guyon’s canal was reduced and the sensory conduction of the UN improved [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The greater incidence on the right side may be because most people are right-handed and perform more repetitive movements using the right hand than the left hand. Some studies have shown that patients with CTS may have UN damage [16,17]. A study by Kang et al found that when patients with CTS underwent carpal tunnel release, the pressure in Guyon's canal was reduced and the sensory conduction of the UN improved [16].…”
Section: Source Of the Curvementioning
confidence: 99%
“…Some studies have shown that patients with CTS may have ulnar nerve damage (13,14). A study found that when patients with CTS underwent carpal tunnel release, the pressure in Guyon's canal is reduced and the sensory conduction of the ulnar nerve improves (13).…”
Section: Discussionmentioning
confidence: 99%
“…The CTS symptoms are mainly sensory in the region of median nerve innervation and median nerve abnormal SCS with or without motor abnormality associated with normal ipsilateral ulnar conduction. Numerous CTS patients had extra-median spread of Earlier electrophysiological studies have shown that traction of nearby ulnar nerve fibers may occur in patients with CTS [3,5,7,8,12,17]. In addition, in an old retrospective study involving the results of 234 cases with CTS, Sedal et al [3] reported that sensory nerve action potential amplitude of ulnar nerve was found to be abnormal in 39.3% of their CTS cases which was associated with increased sensory latency and reduced sensory amplitude of the ulnar nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Guyon's canal (GC) syndrome is an uncommon peripheral neuropathy where the ulnar nerve is entrapped through the narrow canal at the wrist [2]. Many studies analyzed the possible ulnar nerve affection at the region of the wrist in CTS [1], which mainly involved sensory fibers, and that ulnar nerve conduction abnormality was augmented with the increase in the severity of CTS [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%